Phthiracarus (Phthiracarus) ferrugineus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Phthiracarus (Phthiracarus) ferrugineus (C.L. Koch, 1841) * Material – New record for Turkey. One specimen in Trabzon, N 40° 58′ 24.75′′, E 39° 30′ 25.55′′, alt. = 348 m, Yeşiltepe Forest Area, Akçabat. 06 June 2018, trunk of P. abies . Global distribution – Holarctic. Ecology – Forest soils. Note – The species is known to be generally associated with forest soils (Weigmann 2006), however, is recorded for arboricolar habitats as well. It was found abundantly on twigs and leaves of Rhododendron ponticum L. (Murvanidze and Arabuli 2015).

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 258, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Phthiracaridae; Phthiracarus; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Taxonomy; Phthiracarus ferrugineus; 15. Life on land